Tax Law Certainty on The Sale of Food and Beverages after The Enactment of Law Number 1 of 2022 - Josep Irvan Gilang Hutagalung; Dewi Kania Sugiharti; Zainal Muttaqin (Journal of Social Science, 2022)
Taxes on Certain Goods and Services (TCGS) is a concept of integrating consumption-based taxes contained in Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments. The provisions for tax collection in this new law also change local taxation policies, particularly on tax collection on the sale of food and beverages. Therefore, this study aims to analyze the arrangement for collecting TCGS for the sale of food and/or beverages based on the principle of legal certainty and reviewing the implications of the concept of collecting TCGS on the sale of food and/or beverages in terms of local tax intensification efforts. This study uses a normative juridical method using secondary data sources. The data that has been obtained is then described descriptively with qualitative analysis methods. The results of this study indicate that the concept of collecting PBJT for food and beverage sales is in accordance with the principle of legal certainty because it limits the authority to collect VAT by the Central Government and TCGS by the Regional Government for business actors engaged in the culinary industry. To make efforts to optimize regional revenues after the enactment of Law No. 1 of 2022 is to intensify taxes by expanding the revenue base, optimizing the collection process, and increasing supervision.